Synthesis of Co3 O4 /graphene nanocomposite using paraffin wax for adsorption of methyl violet in water. Issue 6 (1st May 2018) - Muralisankar, Indiran; Agilan, Santhanam; Selvakumar, Rajendran; Vairam, Sundararajan
Abstract : This study discusses the use of Co3 O4 impregnated graphene (CoOIG) as an efficient adsorbent for the removal of methyl violet (MV) dye from wastewater. CoOIG nanocomposites have been prepared by pyrolyzing paraffin wax with cobalt acetate. The synthesised nanocomposite was characterised by X‐ray diffraction, field emission scanning electron microscope, transmission electron microscope, Fourier transform infrared spectroscope, Raman spectroscopy, and Brunauer–Emmett–Teller isotherm studies. The above studies indicate that the composites have cobalt oxide nanoparticles of size 51–58 nm embedded in the graphene nanoparticles. The adsorption studies were conducted with various parameters, pH, temperature and initial dye concentration, adsorbent dosage and contact time by the batch method. The adsorption of MV dye by the adsorbent CoOIG was about 90% initially at 15 min and 98% dye removal at pH 5. The data were fitted in Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich and Sips isotherm models. Various thermodynamic parameters like Gibbs free energy, enthalpy, and entropy of the on‐going adsorption process have also been calculated.